If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x-1=3(x+3)
We move all terms to the left:
3(2x-1-(3(x+3))=0
| 4+2x=2(4x+3)-8 | | -3(4-7x)=-96 | | (7)=√5x+4 | | 2x+5=8x+(-7) | | x-68=x+126 | | 2+-3z+1=7 | | 2(2x+5)=0 | | -6d+9+20d=13d+1 | | -4p-3=-7-3p | | 10x-2x^2=-12 | | 3(v-11)=15 | | 3x^{2}-7x=12 | | 99+25.99x=34.99x | | 4(x-7)=3x−5 | | ½(6x-20)=5x+7 | | -5(5.5+3.1x)=-6.2(2.5x+1.9) | | 18x+4=19x-9 | | y+125=y+125 | | 7x+3-3=52-3 | | -7(x+2)=3x-3+3(2x-1) | | 2-(7x-2)+3x=10 | | 11(7+11x)=-36+8x | | 6x+3=-9x-3(x+18) | | 3x+6x+10+5=51 | | K+6=6+k | | -8(1-7n)=440 | | 42-3x=-54+3x | | 119=17y | | -4/x-3=7 | | 5−m4=14 | | -16+4n-19=-13n+16 | | 5x10=3x |